The California Cognitive Assessment Battery (CCAB) - Woods, David; Pebler, Peter; Johnson, David K.; Herron, Timothy; Hall, Kat; Blank, Mike; Geraci, Kristi; Williams, Garrett; Chok, Jas; Lwi, Sandy; Curran, Brian; Schendel, Krista; et al. (Frontiers in Human Neuroscience, 2024)
The California Cognitive Assessment Battery (CCAB) is a collection of 15 non-verbal and 17 verbal subtests normed for remote neuropsychological assessment). The CCAB runs on calibrated tablet computers and can be administered over cellular or Wi-Fi connections, either in the lab or in participants' homes. Spoken instructions and verbal stimuli are delivered through headphones using naturalistic text-to-speech voices. Verbal responses are scored in realtime and digitally recorded for offline transcription using consensus automatic speech recognition (CASR). CASR combines transcripts from seven ASR engines to produce timestamped transcripts that are more accurate than those of any single ASR engine.The CCAB is designed for self-administration and, to assure test validity, is proctored over cellular or Wi-Fi connections using the Examiner, a web-browser based proctoring tool. The Examiner enables test administrators to record timestamped observations, view subtest performance in real time, initiate video chats, and correct potential error conditions (e.g., low power, training failures, failures to begin a subtest, etc.). Here we describe (1) CCAB technology and test design, (2) CCAB usability with older adult participants, (3) CCAB psychometric properties based on normative data from 415 older (ages 50 to 89) participants, and (4) Preliminary results comparing at-home vs. in-lab CCAB administration.